T-2 toxin-induced spatial learning and memory impairment in mice via the gut-brain axis and the intervening effects of resveratrol - Sheng-Quan Su; Gui-Yuan Xiong; Chun-Yan Yao; Xiao-Ling Liu; Yin-Yin Xia; Jin-Yun Long; Xiu-Kuan Li; Liang-Mei Wang; Long Yi; Wu-Wei Xu; Wu-Qiang Lu; Qian-Qian Li; et al. (Ecotoxicology and Environmental Safety)
T-2 toxin, classified as a mycotoxin, harms immune and cognitive systems. Recently, an increasing number of studies have focused on the neurotoxic effects of T-2 toxin. However, there is still a need for a better understanding of the molecular mechanisms involved. In this study, we aimed to elucidate the protective effect of resveratrol (Res) supplementation against T-2 toxin-induced spatial learning and memory impairment and to investigate the communication mechanisms between the gut and the brain. Mice received a single intraperitoneal dose of T-2 toxin (4 mg/kg) followed by Res (100 mg/kg) administered via the same route. The Morris water maze and novel object recognition tests demonstrated that T-2 toxin had a profound negative impact on spatial learning and memory in mice. However, the administration of Res successfully mitigated the cognitive impairments caused by T-2 toxin and notably enhanced the levels of brain-derived neurotrophic factor (BDNF), synaptophysin I (SYN1), and postsynaptic density protein 95 (PSD-95). Moreover, Res demonstrated a protective effect against T-2 toxin-induced damage to hippocampal tissue. Simultaneously, it played a pivotal role in restoring gut microbiota equilibrium and maintaining the integrity of intestinal tight junctions, effectively curbing both localized and systemic inflammation triggered by T-2 toxin exposure. In conclusion, our findings suggest that resveratrol may alleviate T-2 toxin-induced spatial learning and memory deficits, possibly via gut-brain axis modulation.